IMPLEMENTATION OF TRAIT AND FACTOR THEORY IN IMPROVING CAREER PLANNING FOR CLASS XII STUDENTS OF SMA N 4 SUNGAI PENUH IN THE NEW NORMAL ERA - Tiara Maiza Dianti; Mega Iswari; Daharnis (Literasi Nusantara, 2022)
Career counseling guidance is an activity carried out by school counselors in order to help students' career planning, so BK teachers/school counselors need to pay attention to this because it is found in the field that there are students who are still confused in determining the direction of their career which begins with determining the choice of majors in the field. high school program that he will take when he finishes high school. This article, entitled " Implementation of Trait And Factor Theory in Improving Career Planning of Class XII Students at SMA N 4 Sungai Full in the New Normal Era" aims to assist in planning the careers of students at SMA N 4 Sungai Penuh by using trait and factor theory in the new normal era. . This article uses research literature research by collecting theories according to the theme of both reading books and journals.